The hystological and morphometrical analisys of structural changes of the autonomous nerves of the urinary bladder wall in women of early and late menopausal periods. - Bidovanets, B. Yu.; Bodnar, Ya. Ya.; Trach Rosolovska, S. V. (Морфологія / Morphologia / Morfologìâ, 2017)
The overactive bladder is a current issue in world urology research. The morphology patterns are not well investigated yet, especially in menopausal women. Objective. The study presents the results of investigation of qualitative and quantitative changes in autonomous nervous system of the urinary bladder wall in case of its dysfunction in women of early and late menopausal periods. Methods. The study was performed on detrusor specimens of 12 autopsied women with overactive bladder diagnosed before their death. The modified Falk’s method was used for biogenic amines detection. It is based on catecholamines capacity to fluoresce in passing ultraviolet light. For investigation of cholinergic detrusor elements we used our own method, which is based on Crevier-Belanger’s one in Savay-Csillik’s modification – the thiolacetate acid hydrolysis by cholinesterase detects its activity in synapses zones and along all cholinesterase-positive nerve fibers as well. Results. The density of adrenergic and cholinesterase-positive nerve fibers in the urinary bladder wall in women of early menopausal period were decreased on 29,46% and 25% (p<0,05) from control respectively, which means a slight prevalence of parasympathetic innervation. In the late menopausal period the density of adrenergic fibers in this group decreased significantly on 51,16% and 30,77% comparing the control and early menopause groups respectively. The density of the cholinesterase-positive fibers decreased significantly on 30,56% comparing the control group, but the difference between early and late menopause periods was not significant statistically. Conclusion. The progressive sympathetic and parasympathetic denervation of the urinary bladder was detected as well as its dependence of the menopause period. The prevalence of parasympathetic innervation is proven by quantitative analysis. The main factors are the degenerative changes of the autonomous nerves as well as the sclerosis of the parenchyma and the microcirculatory channel system.